Gender-based roles, psychosocial variation, and power relations during delivery and postnatal care: a qualitative case study in rural Ethiopia - Shibeshi, Ketema; Lemu, Yohannes; Gebretsadik, Lakew; Gebretsadik, Abebe; Morankar, Sudhakar (Frontiers in Global Women's Health, 2023)
Introduction The World Health Organization (WHO) strongly encouraged men to support women in receiving maternal healthcare. However, especially in developing countries, maternal healthcare has traditionally been viewed as an issue in women, with men making little or no contribution, even though sexuality and children are shared products. The study aims to understand how gender-based roles, psychosocial variation, and power relations are related to child delivery and postnatal care (PNC) services. Methods The study was conducted in three rural districts of Oromia regional state, Jimma Zone, Ethiopia. An in-depth interview and focus group discussion were held with carefully chosen health professionals, health extension workers, community health development armies, and religious leaders. The data was collected, translated, and transcribed by experienced men and women qualitative researchers. For data analysis, ATLAS.ti version 9 was used. The data were coded and categorized concerning delivery and PNC service utilization. Independent and shared gender-based roles were identified as a means to improve maternal healthcare service delivery. Results The result obtained three categories, namely, gender-based roles, psychosocial variation, and power relations. Men can persuade pregnant women to use delivery services and PNC. The place of delivery is determined by the levels of gender-based power relations at the household level, but women are usually the last decision-makers. The belief of the community that giving birth in a health facility makes women look clean and neat, as opposed to home delivery, increases their intention to use maternal healthcare services. Discussion The study contributes that the role of a man as a husband is crucial in mobilizing others to carry pregnant women to health facilities, contributing to early intervention during labor. The decision-making capacity of women has improved over time, with men accepting their right to make decisions about their health and fetuses. Home delivery and men not being present during delivery are perceived as signs of backwardness, whereas giving birth in health institutes is seen as a sign of modernization and the rights of women.